ANY: Architecture New York (JSTOR)
The bimonthly magazine ANY critically examined architecture, its relationships to other disciplines, and its cultural role in general at the end of the millennium. ANY, the name of which both reads as something undecidable (any magazine) and as an acronym for Architecture New York, involved architects, critics, theorists, sociologists, economists and others from around the world who address issues in architecture that bear on contemporary culture. The publication began in May 1993 and ceased in October 2000 with number 27.
Keywords: Architecture & Architectural History